Phycoremediation of fish farm wastewater by Chlorella sorokiniana and autochthonous microalgae (Research, Society and Development, 2021)
With the disorderly increase in global environmental problems, the cultivation of aquatic organisms is a promising path for sustainable food production. The quality of water, both at the entrance and exit of the production of aquatic animals, needs to be maintained following the parameters specified by local legislation. This study aimed to investigate the removal of contaminants from fish farming wastewater associated with the production of freshwater microalgae biomass. Six completely randomized treatments were used in triplicate: with the addition of microalgae C. sorokiniana in fish farm wastewater (W+Cs), the addition of C. sorokiniana in wastewater enriched with NPK fertilizing (W+F+Cs) or sugarcane vinasse (W+V+Cs), only wastewater (W), wastewater supplemented with fertilizer (W+F) or vinasse (W+V). The wastewater was used in natura to allow the development of autochthonous microalgae. The microalgae C. sorokiniana grew rapidly in effluents enriched with NPK and vinasse. After 28 days of bioassay, the concentrations of several contaminants in the water were reduced: zinc (20 to 88%), lead (5 to 83%), aluminum (56 to 75%), manganese (56 to 72%), cadmium (9 to 52%), calcium (16 to 24%) and magnesium (12 to 33%). Our results indicated that the production of microalgae biomass can be integrated with the treatment of fish farming effluents to reduce the environmental burden and increase the economic bonus for adopting a sustainable production method. However, our results also indicated the importance of introducing a microalgae strain with high productive performance and supplementing the wastewater to obtain rapid biomass.